2021
DOI: 10.1186/s41181-021-00150-z
|View full text |Cite
|
Sign up to set email alerts
|

On site production of [18F]PSMA-1007 using different [18F]fluoride activities: practical, technical and economical impact

Abstract: Background Prostate-specific membrane antigen is overexpressed in prostate cancer and it is considered a good target for positron emission tomography/computed tomography imaging of primary cancer and recurrent/metastatic disease, as well as for radioligand therapy. Different PSMA-analogues labeled with [68Ga]gallium have been investigated, showing excellent imaging properties; however, only small amounts can be produced for each radiolabeling. Recently, a [18F]fluoride labeled PSMA-inhibitor, [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The cost of each single PET/CT exam considered a standard dose of 259 MBq for [ 18 F]PSMA-1007 and of 154 MBq for [ 68 Ga]Ga-PSMA-11. For [ 18 F]PSMA-1007 the presented range of starting activity is the most cost/effective, as previously shown[6].…”
supporting
confidence: 62%
See 3 more Smart Citations
“…The cost of each single PET/CT exam considered a standard dose of 259 MBq for [ 18 F]PSMA-1007 and of 154 MBq for [ 68 Ga]Ga-PSMA-11. For [ 18 F]PSMA-1007 the presented range of starting activity is the most cost/effective, as previously shown[6].…”
supporting
confidence: 62%
“…Conversely, the limit of low starting activity does not apply to the production of fluorinated PSMA inhibitors. The starting activity range of [ 18 F]Fluoride plays a key role in the final yield for [ 18 F]PSMA-1007; thus, the optimization of the variables influencing the yields of the synthesis is mandatory as we have previously demonstrated [6]. In fact, using different starting activities of [ 18 F]Fluoride: low (55.91 ± 6.69 GBq), medium (89.06 ± 4.02 GBq), and high (162.38 ± 6.46 GBq), we found that the medium one was the most compliant for clinical needs, ensuring the best match of RCY, costs, and number of performed PET/CT exams [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the half-life of 68 Ge/ 68 Ga generators is 271 days, they can offer a maximum activity of 1.85 GBq for 68 Ga, and they can only scan in a limited number of prostate cancer patients . For a higher number of patients in several PET centers with the characterization of 18 F, 18 F-labeled diagnostic radiopharmaceuticals targeting PSMA have several advantages. , An on-site cyclotron produces large-scale 18 F without several productions, and 18 F has a longer half-life (109.8 min) and lower positron energy (0.65 MeV, 96.7% β + ), which increases the theoretical maximum spatial resolution. , …”
Section: Introductionmentioning
confidence: 99%